Efektivitas Case-Based Learning (CBL) Terhadap Pemahaman Konsep Ekonomi Siswa SMA: Systematic Literature Review (SLR) - Wahyu Muh. Syata (Jurnal Ilmiah Literasi Indonesia, 2026)
Economic education at the Senior High School (SMA) level plays a strategic role in equipping students with an understanding of economic concepts and principles relevant to everyday life. However, various studies indicate that high school students' understanding of economic concepts remains relatively low, characterized by weak abilities in answering questions with high cognitive levels (C4 and above) and a tendency for learning to end in rote memorization without deep comprehension. This study aims to systematically examine the effectiveness of Case-Based Learning (CBL) on high school students' understanding of economic concepts. The method used is a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Literature searches were conducted on five academic databases (Google Scholar, Scopus, SINTA, Garuda, and DOAJ) with publication range 2019–2026. The synthesis results from various studies show that CBL is proven effective in improving high school students' understanding of economic concepts. This effectiveness is reflected in the improvement of critical thinking skills deeper conceptual understanding, as well as increased active engagement and student learning motivation. The success of CBL is inseparable from the characteristics of this approach that uses real-life scenarios, encourages critical analysis, and actively involves students in the learning process. However, the implementation of CBL in the field still faces various challenges, particularly related to teacher readiness, resource limitations, and the dominance of teacher-centred approaches. Technology integration and the development of CBL-based learning materials are potential strategies to optimize the effectiveness of this method. Further research with more diverse designs, longer durations, and broader sample coverage is still needed to provide a more comprehensive picture.